Pacted Transition to Democracy: The Case of Mozambique - Pekka Virtanen (Modern Africa, 2016)
The findings of “third wave” studies on democratic transitions in Southern Europe and Latin America from the 1970s suggested that a democratic outcome is most likely when contending parties are relatively equal and elites make a pact to navigate the transition process. However, later studies of post-communist transitions do not support this inference. This paper analyses the transition process in Mozambique, a former “Afro-communist” regime, during the early 1990s. The findings show that – contrary to the conclusions drawn from the “third wave” studies – in Mozambique the pact concluded in the context of the peace accord of 1992, which ended a sixteenyear civil war, had contradictory results in terms of democratisation. While the political situation has been relatively stable until recent years, the country has moved toward competitive authoritarian rule instead of full democracy. The main explanatory factor for this trend appears to be the cohesion of the ruling party, which in the case of Mozambique derives from its origins in armed liberation struggle. Renewed incidents of political violence over the last few years also cast doubt on the durability of political stability.